2021
DOI: 10.12998/wjcc.v9.i22.6300
|View full text |Cite
|
Sign up to set email alerts
|

Jumbo cup in hip joint renovation may cause the center of rotation to increase

Abstract: BACKGROUND Utilizing the large jumbo cup in revision total hip arthroplasty is an effective approach to cure many lacunar and segmental peripheral bone defects. However, with the use of the jumbo cup, the center of the hip joint may become elevated relative to the primary acetabulum, and the diameter of the large cup is greater. AIM To study the height and the significance of the elevation of the hip joint center. METHODS Eighty-eight patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…However, the current study confirmed that the use of the jumbo cup still leads to a HCOR upshift, particularly in AAOS III patients, which reminds surgeons that the use of the jumbo cup technology in more severe acetabular bone defects requires in-depth consideration as it may change hip biomechanics, increase the risk of component loosening, and increase the need of re-revision surgery ( Delp et al, 1996 ; Peng et al, 2021 ). Of course, these negative effects can be averted through technological advancements in the development of prostheses, such as improving the friction interface ( Hu et al, 2015 ) and increasing the length of the femoral head ( Woelfle et al, 2014 ).…”
Section: Discussionsupporting
confidence: 73%
“…However, the current study confirmed that the use of the jumbo cup still leads to a HCOR upshift, particularly in AAOS III patients, which reminds surgeons that the use of the jumbo cup technology in more severe acetabular bone defects requires in-depth consideration as it may change hip biomechanics, increase the risk of component loosening, and increase the need of re-revision surgery ( Delp et al, 1996 ; Peng et al, 2021 ). Of course, these negative effects can be averted through technological advancements in the development of prostheses, such as improving the friction interface ( Hu et al, 2015 ) and increasing the length of the femoral head ( Woelfle et al, 2014 ).…”
Section: Discussionsupporting
confidence: 73%
“…The literature search initially identified 101 articles and finally included 19 articles in this systematic review according to the inclusion and exclusion criteria ( 31 49 ) ( Figure 1 ). Among the 19 articles, 2 articles were pure radiological studies ( 31 , 40 ).…”
Section: Resultsmentioning
confidence: 99%
“…The literature search initially identified 101 articles and finally included 19 articles in this systematic review according to the inclusion and exclusion criteria ( 31 49 ) ( Figure 1 ). Among the 19 articles, 2 articles were pure radiological studies ( 31 , 40 ). There were three pairs of cognate articles (six articles) that were published in different years ( 38 , 39 , 41 , 45 , 48 , 49 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations